Kierkegaard's “Anti-Rationalism” in the Service of Reason and Faith: A Response to the Hegelian System - Godfrey, James (Pacifica, 2004)
This article explores the prevailing understanding that Kierkegaard's criticism of the Hegelian system constitutes an attack against reason as such. As paradox is encountered through reason, I look to Hegel in order to discover Kierkegaard. In this way the inadequacies of Hegel's idealism, revealed in his philosophical formulation of the incarnation, demonstrate the necessity of Kierkegaard's existentialism, expressed in terms of ‘faith’. By this means one may begin to revise any dualistic notions of faith and reason as competing alternatives for articulating the Christian vision.